2021
DOI: 10.3390/cancers13071739
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Mechanism of miR-877-3p Could Provide Potential Biomarkers and Therapeutic Targets in Squamous Cell Carcinoma of the Cervix

Abstract: No therapeutic targets and molecular biomarkers are available in cervical cancer (CC) management. In other cancer types, micro-RNA-877-3p (miR-877-3p) has been associated with events relevant for CC development. Thus, we aimed to determine miR-877-3p role in CC. miR-877-3p levels were examined by quantitative-PCR in 117 cervical lesions and tumors. Effects on CC cell proliferation, migration, and invasion were evaluated upon anti-miR-877-3p transfection. miR-877-3p dependent molecular mechanism was comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Saioa Mendaza et al experimentally found that mir-877-3p promotes Squamous Cell Carcinoma of the Cervix (SCCC) cell migration and invasion by regulating cytoskeletal protein folding, mainly through the CCT complex, and that antimir-877-3p increased the expression of CCT3 in SCCC, leading to abnormal folding of actin and microtubulin, thereby impairing cell migration and invasion ability. Overall, CCT3 may be considered a new and promising biomarker that is closely related to the progression, prognosis, and survival of CESC and may become a therapeutic target for CESC (26).…”
Section: Cervical Cancermentioning
confidence: 99%
“…Saioa Mendaza et al experimentally found that mir-877-3p promotes Squamous Cell Carcinoma of the Cervix (SCCC) cell migration and invasion by regulating cytoskeletal protein folding, mainly through the CCT complex, and that antimir-877-3p increased the expression of CCT3 in SCCC, leading to abnormal folding of actin and microtubulin, thereby impairing cell migration and invasion ability. Overall, CCT3 may be considered a new and promising biomarker that is closely related to the progression, prognosis, and survival of CESC and may become a therapeutic target for CESC (26).…”
Section: Cervical Cancermentioning
confidence: 99%
“…The role of let-7a-5p and miR-877-3p in the endometrium is undefined. In cancer, let-7a-5p has been shown to inhibit migration, invasion and epithelial–mesenchymal transition, and miR-877-3p promoted cell proliferation and differentiation ( Duan et al 2019 , Mendaza et al 2021 ). We postulate that these miRNAs fine-tune the endometrial transcriptional response to menstrual hypoxia to ensure timely repair of the denuded endometrial surface and limit menstrual blood loss.…”
Section: Research Lettermentioning
confidence: 99%